Nurses’ perspectives on working conditions while caring for patients with COVID-19 during the epidemic threat in Poland - Sierpińska, Lidia Elżbieta; Mikołajewska, Monika; Araminowicz-Kierklo, Elżbieta; Rydzik, Łukasz; Makarska-Białokoz, Magdalena; Czarny, Wojciech (Frontiers in Public Health, 2025)
IntroductionThe severe state of health of patients with coronavirus disease 2019 (COVID-19) has increased the risk of arduous and hazardous work conditions for nurses. The aim of this study is to identify the conditions of nurses’ work during the care of patients with COVID-19 during the state of epidemic threat.MethodsThe COVID-19 pandemic has significantly impacted the healthcare system, especially that of frontline nurses. This study aimed to assess the work conditions and psychological stress experienced by nurses during the pandemic. This study included 116 nurses who provided care to patients with COVID-19 in hospital wards. A random sampling method was employed to select participants from among those working in the shift system. A diagnostic survey method was used to collect data, with a focus on work conditions, stress exposure, and the provision of personal protective equipment (PPE). Data analysis was performed using SPSS v.29 (Statistical Package for the Social Sciences, Version 29), and chi-squared and Fisher’s exact tests were applied.ResultsOf the total nurses, 69.0% reported that they were ‘sometimes’ provided with personal protective equipment. According to 60.3% of participants, nurse staffing was provided in accordance with regulations ‘sometimes.’ A total of 64.7% of the participants experienced stress: concern about infection with SARS-CoV-2, severe health status of patients, patient death, and shortage of equipment. The main complaints related to stress were difficulty concentrating, sleep problems, and headaches; 69.8% of the participants were exposed to hazardous factors at work, and 69.0% experienced arduous factors. Shortages of medical equipment were reported, mainly because of the lack of respirators, cardiac monitors, and inhalators.ConclusionNurses employed in hospital wards during the care of patients with COVID-19 worked under difficult conditions. Sometimes, they were provided with personal protective equipment, and sometimes, nurse staffing was provided in accordance with regulations. There was significant exposure to stress, hazardous and arduous factors, and shortages of medical equipment.